Blood Profile of Quails (Coturnix coturnix japonica) Fed Ration Containing Silkworm Pupae (Bombyx mori) Powder Extract - Novita Anggraeni; Achmad Farajallah; Dewi Apri Astuti (Faculty of Animal Science, Bogor Agricultural University, 2016)
The aim of this research was to assess the use of silkworm pupae (Bombyx mori) powder extract on the blood cells and hematological variables of quails (Coturnix coturnix japonica). The treatments consisted of R0= isoenergy and isoprotein ration without pupae powder extract, R1= isoenergy and isoprotein ration + 1% of pupae powder extract, R2= isoenergy and isoprotein ration + 10% of pupae powder extract, R3= isoenergy and isoprotein ration + 1% of residue of pupae powder extract, R4= isoenergy and isoprotein ration + 10% of residue of pupae powder extract, R5= isoenergy and isoprotein ration + 1% of pupae powder, and R6= isoenergy and isoprotein ration + 10% of pupae powder. The variables measured were blood cell and hematological profiles including the number of leukocytes, erythrocytes, and leukocytes differentiation. Immune response was observed at 12, 24, and 48 h by counting the white blood cells type. The results showed that feed consumption ranged 79.19-154.70 g/quail/wk and the body weight was 71.45-149 g/quail. The addition of pupae extract at a dose of 10% in the diet significantly (P<0.05) increased the number of quail white blood cells. The addition of pupae extract, pupae powder residue, and pupae powder in the ration did not significantly affect the number of quail erythrocytes, hemoglobin, and PCV (packed cell volume). Mean number of white blood cells increased during 24 h after treatment of 10% pupae powder extract (R2) and decreased at the 48th h. It is concluded that the value of leukocytes, lymphocytes, monocytes, and heterophile increased in quails supplemented with 10% pupae powder extract (R2).